Minor Pulses- The Overlooked Key for Food Security and Sustainable Development - Baruah, Bhanita; Naik, M. Ramesh; Teja, R. Ravi (Chronicle of Bioresource Management, 2020)
Minor pulses, often overlooked in mainstream agriculture, are the underutilized and lesser-known pulses which could play a vital role in enhancing food security, improving nutrition and promoting sustainable farming practices. These pulses, including horse gram, moth bean, lablab bean, and others, are highly nutritious, climate-resilient, and require minimal inputs, making them an ideal choice for marginal lands. Despite their advantages, the cultivation of minor pulses in India faces several challenges, such as low productivity, biotic and abiotic stresses, limited research and development, inadequate mechanization, and poor market accessibility. By integrating minor pulses into mainstream agricultural systems and promoting their consumption, India can make significant progress toward ensuring food security, reducing malnutrition, and supporting climate-resilient agriculture.